Students’ Self-Efficacy Belief as a Predictor of Academic Performance - Norsuhaily, Abu Bakar (2016)
This study examines the role of students’ self-efficacy belief and how it affects and predicts their academic performances. The objectives of the study are to examine the relationship between students’ self-efficacy belief and academic performance. Similarly, the study aims to explore the predictability power of students’ self-efficacy belief in predicting students’ academic performance. A total of 364 undergraduate students from University Sultan ZainalAbidin (UniSZA) Terengganu Malaysia, participated in the study. A questionnaire was used in soliciting information from the sample respondents. Academic performance was measured using academic GPA collected from all the participants. Obtained data was analyzed using correlation and regression analysis. Findings of the study revealed that UniSZA undergraduate students are self-efficacious in their learning, the study also revealed that a strong positive correlation exist between students’ self-efficacy belief and academic performance while students’ self-efficacy belief serves as a good predictor of students’ academic performance.